From planation surface to Holocene climate pulses: the evolution of landscape in plateau reliefs - Moreira, Vinícius Borges; Perez Filho, Archimedes (Sociedade & Natureza, 2020)
In the central portion of Brasil there are extensive and continuous plateau of flat surface, which are presented in a staggered way, separated by embedded fluvial valleys, among which the Uberlândia-Uberaba plateau stands out in the region of Triângulo Mineiro - MG. On this, geomorphological features such as veredas and summit depressions populated by murundus, commonly associated to the drainage network in tabular relief, understood here as key environments for paleoenvironmental interpretation. To characterize and understand the processes of formation of these environments and their evolution in the landscape, morphometric indexes, topographic profiles and evolutionary models of landscape were elaborated, presenting a general panorama and demonstrating the importance of geomorphological elements and landscapes from Paleogene planation surfaces to the Holocene climatic pulses